Minimally Invasive Esophagectomy Is Associated with Superior Survival Compared to Open Surgery. Issue 5 (May 2023) - Ising, Mickey S.; Smith, Susan A.; Trivedi, Jaimin R.; Martin, Robert C.G.; Phillips, Prejesh; Van Berkel, Victor; Fox, Matthew P.
Introduction: Minimally invasive esophagectomy (MIE) has not been associated with a long-term survival advantage compared to open esophagectomy (OE). We investigated survival differences between MIE, including laparoscopic and robotic, and OE. Methods: Patients undergoing esophagectomy from 2010 to 2014 with T1-4 N0-3 M0, adenocarcinoma or squamous cell histology, in middle or lower esophagus were queried from the National Cancer Database and stratified into groups based on their surgical procedure: robotic, laparoscopic, or OE. Propensity matching (1:1) was done between robotic and laparoscopic to produce an MIE group. The MIE group was matched to OE yielding a 1:1:2 matching of robotic:laparoscopic:OE. Postoperative outcomes and survival (Kaplan-Meier) were compared between groups. Results: Prior to matching, 7, 163 patients met inclusion criteria and a greater portion underwent OE (67.7%) than MIE (laparoscopic 24.9% and robotic 7.4%). Matching yielded similar groups (robotic = 527, laparoscopic = 527, and OE =1054). Compared to OE, MIE patients had a significantly greater number of nodes sampled and trended toward increased R0 resections (96.1% vs 94.3%, P = .053). OE was associated with a longer median postoperative stay (10 vs 9 days, P = .001). Mortality at 30 and 90 days was similar . However, postoperative survival for MIE was significantly greater than OE ( P < .001). No survival difference existed between robotic and laparoscopic ( P = .723). Conclusions: MIE is associated with increased number of nodes examined and a shorter postoperative length of stay. After propensity matching, patients undergoing MIE had better long but not short-term survival than OE. This benefit seems to be independent of the use of robotic technology.